Micro-impact testing of AlTiN and TiAlCrN coatings - Beake, Ben D.; Isern, Luis; Endrino, José L.; Fox-Rabinovich, German S. (Elsevier, 2018)
A novel micro-scale repetitive impact test has been developed to assess the fracture resistance of hard coatings under dynamic high strain rate loading. It is capable of significantly higher impact energies than in the nano-impact test. It retains the intrinsic depth-sensing capability of the nano-impact test enabling the progression of the damage process to be monitored throughout the test, combined with the opportunity to use indenters of less sharp geometry and still cause rapid coating failure. The micro-impact test has been used to study the resistance to impact fatigue of Al-rich PVD nitride coatings on cemented carbide. The impact fatigue mechanism has been investigated in nano- and micro-scale impact tests. Coating response was highly load-dependent. A Ti0.25Al0.65Cr0.1N coating with high H3/E2 performed best in the nano- and micro- impact tests although it was not the hardest coating studied. The role of mechanical properties, microstructure and thickness on impact behaviour and performance in cutting tests is discussed.
Keywords: AlTiN; PVD; TiAlCrN; Fracture resistance; Micro-impact